Changes of the maximal strength potential of the flexor muscles in the elbow joint after six weeks of programmed workout with standard and modified repetitive efforts done by the students of the Faculty for Physical Culture in Skopje - Vuksanovikj, Vladimir (Faculty of physical education, 2008)
The research analyses the changes of the maximal strength potential of the muscles flexors in the elbow joint, as well as the anthropometric measures and bio-mechanic variable covered by the work programme. The conducted workout programme was of longitude character, with time duration of six weeks and two time zones for control of the changes. The same was conducted on 51 students of the Faculty of Physical Culture in Skopje. The students were divided into three experimental groups (previously homogenized), who had tasks to conduct work strength exercises at the Scot’s bench, for the included muscles, with individual outer weight (dumbbell). Each of the groups practices various performance methods of the muscles’ contractions. The first experimental group have worked according to the matrix exercise method. The second experimental group have worked with shortened amplitude in the elbow joint, in the zone from the semi flexion to the maximal flexion and vice versa. The third group assignment was also to work with the shortened amplitudes in the elbow joint, however performed in a manner of maximal extension up to the semi flexion and vice versa. The analysis and the statistical processing of the results (ANOVA/MANOVA) have shown positive changes in the maximal strength capacities within the participants from all three experimental groups. Non-existence of the differences in the results gained by the transversal check (control and final testing), have presented similar behaviour of the strengths capacities of the respondents in each of the groups, although they all have worked under different model of movement performance in the elbow joint. The findings support the transformation programmes of the human performance abilities and are directly focused towards the modification of the strength component.
Промена на максималниот силов потенцијал на флексорите на зглобот на лакoтот по шест неделено програмирано вежбање со стандардни и модифицирани репетитивни напрегања кај студентите од Факултетот за физичка култура во Скопје
Keywords: exercise, maximal strength, amplitude, elbow joint, matrix method, semi flexion, repetition, angular speed, anthropometry, experimental groups, longitudinal.